The effects of organizational climate on the privet institutions in the Sultanate of Oman: a theoretical foundations study = المناخ التنظيمي وأثره في المؤسسات الخاصة بسلطنة عمان: دراسة في الأسس النظرية سيف بن عبد الله بن سنان الهنائي - Sinan, Saif Abdullah; Zakaria, Abd. Wahab; Ibrahim, Mohd Burhan (International Organization Center of Academic Research (OCERINT), 2020)
This article discusses the theoretical foundations of the organizational climate. It is part of a field study conducted by the researcher in the private institutions of the Sultanate of Oman. The problem is that the organizations' lack of awareness of the importance of the prevailing organizational climate in them, and reviewing it from time to time despite the close link between it and organizational development, stimulating the creative behavior of workers and the motivations of workers and raising their level of morale and improving the level of their performance; has formed a problem that deserves attention and research. Therefore, the objectives of the study are: to identify the characteristics and significance of the organizational climate; diagnosing the types of organizational climate and the factors affecting it. To present organizational climate models. The descriptive method was used to identify the characteristics, significance, types and models of the organizational climate. The findings of the study indicated: that the organizational climate is a mediator between job requirements and the needs of the individual and that job satisfaction is part of the organizational climate. The importance of the organizational climate to produce and demonstrate the organization's ability to achieve its goals is demonstrated. The control and control to properly direct the elements of the organizational climate enable the organization's management to motivate individuals and push them towards hard work. There are several factors that affect the organizational climate: material and economic resources, specific administrative policies for selection, promotions, and wages, professional values for administrators and employees, flexible and open organizational structures. ************************************************************************** يناقش هذا المقال الأسس النظرية للمناخ التنظيمي، وهو جزء من دراسة ميدانية يجريها الباحث في المؤسسات الخاصة بسلطنة عمان. تكمن المشكلة في إن عدم إدراك المنظمات لأهمية المناخ التنظيمي السائد فيها، ومراجعته من وقت لآخر رغم الصلة الوثيقة بينه وبين التطوير التنظيمي، وحفز السلوك الإبداعي لدى العاملين ودوافع العاملين ورفع مستوى الروح المعنوية لديهم وتحسين مستوى أدائهم؛ قد شكل مشكلة تستحق العناية والبحث. لذا هدفتْ الدراسة: التعرف على خصائص المناخ التنظيمي وأهميته. تشخيص أنواع المناخ التنظيمي والعوامل المؤثرة فيه. عرض نماذج المناخ التنظيمي. تم استخدام المنهج الوصفي للتعرف على خصائص المناخ التنظيمي وأهميته، وأنواعه، ونماذجه. أشارت نتائج الدراسة: أنَّ المناخ التنظيمي وسيط بين متطلبات الوظيفة وحاجات الفرد وأن الرضا الوظيفي جزء من المناخ التنظيمي. تظهر أهمية المناخ التنظيمي على إنتاج وقدرة المنظمة على تحقيق أهدافها. أن التحكم والسيطرة لتوجيه عناصر المناخ التنظيمي توجيها صحيحاً تمكن إدارة المنظمة من تحفيز الأفراد ودفعهم نحو العمل الجاد. وجود عدة عوامل تؤثر في المناخ التنظيمي هي: الموارد المادية والاقتصادية، السياسات الإدارية المحددة للاختيار والترقيات والأجور، القيم المهنية للإداريين والعاملين، الهياكل التنظيمية المرنة والمفتوحة.